The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsaelm.2c00306
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Ultrahigh-Performance Near-Infrared Photoresponsive Field-Effect Transistor Using a Lead Phthalocyanine/MoS2 Organic–Inorganic Planar Heterojunction

Abstract: We report a near-infrared (NIR) photoresponsive field-effect transistor that has an organic–inorganic planar heterojunction using lead phthalocyanine (PbPc)/MoS2. In the presence of NIR illumination of 0.061 μW/cm2 at 808 nm, ultrahigh photoresponsivity and external quantum efficiency were obtained, which were 1263.85 A W–1 and 194066.7%, respectively, which were much larger than those of the reference devices, when the gate voltage and drain voltage were set to 50 V using Al as the source and drain electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Photodetectors with bipolar charge transport characteristics have been developed, 177 and highly stable NIR photodetectors have been proposed. 178,179 The suppression of dark current has seen recent developments, with dark currents reduced to the pA level. 180 In contrast to heterojunctions, bilayer structures with independent channels can individually transport photogenerated excitons.…”
Section: Mos 2 -Based Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodetectors with bipolar charge transport characteristics have been developed, 177 and highly stable NIR photodetectors have been proposed. 178,179 The suppression of dark current has seen recent developments, with dark currents reduced to the pA level. 180 In contrast to heterojunctions, bilayer structures with independent channels can individually transport photogenerated excitons.…”
Section: Mos 2 -Based Photodetectorsmentioning
confidence: 99%
“…However, PbPc demonstrates excellent photovoltaic response in the NIR region. Under a mere 0.061 mW cm À2 NIR illumination, PbPc/MoS 2 179 exhibits an exceptionally high photoresponsivity (1263.85 A W À1 ) and an extraordinarily high EQE (194 066.7%). This is attributed to the use of aluminum electrodes.…”
Section: Mos 2 -Based Photodetectorsmentioning
confidence: 99%
“…In 2006, Kageyama et al [ 95 ] investigated that OLED ( Figure 8 ) using tris(8-quinolinolato)aluminum (Alq 3 ) highly doped with N,N′ -bis(neopentyl)-3,4:9,10-perylenebis(dicarboximide) ( M1 ) as an emitting layer exhibit near-infrared EL with a peak at 805 nm originating from M1 aggregates ( Figure 9 ). Phthalocyanines are known to be organic semiconductors and have attracted much attention because of their high chemical stability, various synthetic modifications, epitaxial growth of thin films by organic molecular beam epitaxy and unique absorption bands extending from the ultraviolet region to infrared region [ 96 , 97 ]. Cheng et al [ 98 ] reported the OLED device used purple phthalocyanine ( M2 ) single crystal as an active light-emitting layer with the emission of 936 nm ( Figure 9 ).…”
Section: Nir Fluorescent Materials Based On Small Moleculesmentioning
confidence: 99%
“…[8,9] To achieve target-oriented electronic properties of transistors, numerous studies have been conducted to improve functions or performance (such as mobility, threshold voltage, on/off ratio, operational voltage, hysteresis window, and photoresponsivity) by adding or customizing specific layers while maintaining the device structure. [10][11][12][13] It is well known that the performance of a transistor is strongly related to the quality of both the semiconductor and gate dielectrics, as well as the interface between them. Achieving An organic nano-floating-gate transistor (ONFGT) with both photosynaptic and electrical memory functions is developed using a perovskite (CsPbBr 3 ) NCinsulating polymer (polystyrene; PS) nanocomposite and CsPbBr 3 NCs as the tunneling and floating gate layers, respectively.…”
Section: Introductionmentioning
confidence: 99%